Economic Crisis and Informatisation Strategies of Enterprises : Results of Comparative Surveys from Years 2009-2010 - Dyczkowski, Mirosław (Kryzys ekonomiczny a strategie informatyzacji przedsiębiorstw : wyniki ankietowych badań porównawczych z lat 2009-2010, 2010)
he materials of the AITM’2009 Conference contained results of the survey – carried out by the author of this paper in 2009 – which aimed at analysing how the recent economic crisis influenced informatisation strategies of enterprises [Dyczkowski 2009]. In 2010 a comparative study was conducted, with an objective to determine whether any substantial differences in reference to the previously obtained results could be observed, and if yes, how intensive such changes were. This paper discusses results of the comparative surveys from the years 2009-2010. The results obtained support a working hypothesis that the economic crisis affected – to smaller or greater extent – short- and long-range informatisation strategies in the majority of companies or institutions. The detailed information to that subject is included in this paper.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 101-1017
Keywords: statistical analysis; informatisation strategies; comparative survey results